Electronic Word of Mouth as a Predictor of Purchase Intention: Evidence from Instagram and TikTok in Indonesia - Pratama, Chikal Adi; Astarini, RR Dyah (International Journal of Digital Entrepreneurship and Business, 2023)
In contemporary times, the social media landscape is shaped by the dominance of Instagram and TikTok. These two platforms are prominently used for marketing various products and services. Therefore, this research aimed to examine the influence of electronic word of mouth (e-WOM) on purchase intention for e-WOM recipients on Instagram and TikTok. The dimensions tested include quality, quantity, credibility, and information provider expertise. In this context, the quantitative research analyzed the causal relationships based on the developed hypotheses. The purposive sampling method used was guided by specific criteria, namely individuals who were users of Instagram and TikTok, encountered e-WOM communication through these platforms, specifically originated from influencers, and refrained from making purchases of particular products or services. Furthermore, data analysis was conducted using the Multiple Linear Regression statistical instrument. The results showed that e-WOM quality, quantity, credibility, and information provider expertise positively influenced purchase intention. This research had managerial implications, indicating the need to enhance e-WOM quality, quantity, credibility, and information provider expertise to increase purchase intention on product or service influencers communicate. The implications included increasing the number of reviews, summarizing the product or service, improving recommendation ratings, enhancing confidence, and improving the ability to evaluate the products or services.